Erythrocyte Indices for Beta-thalassemia Trait (BTT) Screening in Indonesia: A Scoping Review - Iffa Mutmainah; Asri Ragil Kemuning; Widya Eka Nugraha; Aisyah Amanda Hanif; Anna Vipta Resti Mauludyani (Diponegoro International Medical Journal, 2025)
Background: Thalassemia is a monogenic disorder that ranks fifth among the catastrophic diseases in Indonesia. Thalassemia screening plays an important role in preventing the birth of individuals with thalassemia major. Numerous erythrocyte indices have been used as first-line screening methods for beta-thalassemia trait, preceding definitive analysis using hemoglobin electrophoresis.Objective: This study aimed to conduct a literature review comparing the most frequently used erythrocyte indices in Indonesia with hemoglobin electrophoresis.Methods: A systematic search was conducted using PubMed, Scopus, EBSCO, and Google Scholar databases in July 2024. This study included full-text articles in Indonesian or English that compared erythrocyte indices and hemoglobin electrophoresis for thalassemia screening.Results: Six articles were included in this review. Two of the six articles analyzed the compatibility of erythrocyte indices and hemoglobin electrophoresis using kappa statistics. The remaining articles calculated the diagnostic values.  Among the ten erythrocyte indices, the Mentzer index was the most frequently assessed, appearing in six studies, followed by the indices of Shine & Lal and Sirdah, each evaluated in three studies. The Green-King, England & Fraser, and Srivastava indices were each examined in two studies. Additionally, Ehsani, Matos and Carvalho, RDW, and MCV and/or MCH indices were each assessed in one study.Conclusion: The compatibility between erythrocyte indices and hemoglobin electrophoresis, based on two studies, was fair indicating that hematological indices alone are insufficient for a definitive diagnosis. This finding aligns with the conclusions of four other studies, which also suggested that no single erythrocyte index is definitive. Among the indices, the Green-King Index demonstrated the highest reliability; however, further studies are needed to support this finding, while hemoglobin electrophoresis remains essential for an accurate diagnosis.